The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1074/jbc.m310867200
|View full text |Cite
|
Sign up to set email alerts
|

Outer Dense Fibers Serve as a Functional Target for Cdk5·p35 in the Developing Sperm Tail

Abstract: Cdk5 is ubiquitously expressed in all tissues, but its activators, p35 and p39, are principally found in brain, and Cdk5 activity has mostly been associated with brain development, particularly neuronal differentiation and migration. Here we show that the p35 transcript and protein are also present in the testis, and an active Cdk5⅐p35 complex exists in this tissue as well. Cdk5 and p35 are prominently observed in elongating spermatid tails, particularly over the tail outer dense fibers (ODF). The appearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 52 publications
(47 reference statements)
1
36
0
Order By: Relevance
“…23 Recently, several studies have shown that CDK5 plays an important role in the exocytosis, differentiation, and senescence of nonneuronal cells such as pancreatic ␤ cells, 24,25 monocytes, 26 muscle cells, 27 and testis. 28 For example, CDK5 regulates glucose-induced insulin exocytosis by phosphorylating Munc18 25 or the L-type voltage-dependent calcium channel 24 in pancreatic ␤ cells. In muscle cells, CDK5 phosphorylates nestin, the intermediate filament protein, which plays an important role in muscle development and regeneration.…”
Section: Figurementioning
confidence: 99%
“…23 Recently, several studies have shown that CDK5 plays an important role in the exocytosis, differentiation, and senescence of nonneuronal cells such as pancreatic ␤ cells, 24,25 monocytes, 26 muscle cells, 27 and testis. 28 For example, CDK5 regulates glucose-induced insulin exocytosis by phosphorylating Munc18 25 or the L-type voltage-dependent calcium channel 24 in pancreatic ␤ cells. In muscle cells, CDK5 phosphorylates nestin, the intermediate filament protein, which plays an important role in muscle development and regeneration.…”
Section: Figurementioning
confidence: 99%
“…Cdk5 is most abundant in neurons and its activators, p35 and p39, have been presumed to be neuronspecific. Although Cdk5 activity has generally been associated with brain, recent studies have implicated a role for Cdk5 in other tissues such as muscle (11,12), ocular lens (13), and testis (14). It seems that Cdk5 modulates cell differentiation and certain cellular functions.…”
mentioning
confidence: 99%
“…Cdk5 requires its regulatory partner, p35 (or its potent truncated form, p25) (Lew and Wang, 1995;Lee et al, 1997) or its isoform, p39 (Tang et al, 1995) for activity. Although Cdk5 activity has mostly been associated with brain, more recent studies indicate that Cdk5 plays an important role in other tissues as well such as muscle (Sahlgren et al, 2003), ocular lens (Gao et al, 2002) and testis (Rosales et al, 2004b (Inada et al, 1999;Cheng et al, 2000;Lee et al, 2005). Indeed, vimentin is phosphorylated by protein kinase A, protein kinase C, and CaMKII at specific serine sites (Izawa and Inagaki, 2006) and this has been associated with disassembly of the vimentin intermediate filaments (Eriksson et al, 1992).…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…Cdk5 requires its regulatory partner, p35 (or its potent truncated form, p25) (Lew and Wang, 1995;Lee et al, 1997) or its isoform, p39 (Tang et al, 1995) for activity. Although Cdk5 activity has mostly been associated with brain, more recent studies indicate that Cdk5 plays an important role in other tissues as well such as muscle (Sahlgren et al, 2003), ocular lens (Gao et al, 2002) and testis (Rosales et al, 2004b). It appears that Cdk5 regulates cell differentiation and certain specialized cell functions (Rosales and Lee, 2006), including wound healing (Gao et al, 2004), gene transcription (Fu et al, 2004), senescence (Alexander et al, 2004), and secretion (Rosales et al, 2004a).…”
mentioning
confidence: 99%